PENERAPAN TEKNIK MENGHARDIK DAN TERAPI AFIRMASI POSITIF PADA PASIEN DENGAN HALUSINASI PENDENGARAN - Pamungkas, Tryan Bayu; Riyana, Asep; Hartono, Dudi (Fakultas Ilmu Kesehatan Universitas Siliwangi, 2025)
Based on data from the Sindangkasih Health Center, the number of cases of severe mental disorders, namely schizophrenia, is 43 cases from all cases of mental disorders. This case study is to determine the effectiveness of the application of rebuke therapy and positive affirmation therapy on hallucinations in patients with sensory perception disorders: Auditory Hallucinations. Schizophrenia is a neurological disease that affects the patient's perception, way of thinking, language, emotions, and social behavior. Hallucinations are a condition where an individual loses the ability to distinguish between stimuli (thoughts) and external stimuli (the outside world). The method used in this Scientific Paper is qualitative in the form of a comparative case study on two respondents. The implementation of this case study was carried out by means of a home visit to the homes of both respondents, the interventions given were in the form of rebuke techniques and positive affirmation therapy for 5 days of nursing to reduce the signs and symptoms of hallucinations. There was a decrease in signs and symptoms in both respondents after being given intervention, signs and symptoms in client 1 decreased from the initial 24 to 11, while in client 2 decreased from the initial 33 to 24. The technique of reprimanding and positive affirmation therapy is very influential in reducing signs and symptoms of hallucinations, this intervention can be done independently or assisted by family. Suggestions for the provision of reprimanding techniques and positive affirmation therapy can be further increased as an effort to control hallucinations.